Indoor Environmental Quality in a Classroom: Faculty of Architecture, Chiang Mai University - Chindapol, Sumavalee (Journal of Architectural/Planning Research and Studies (JARS), 2019)
This study investigates indoor environmental quality of a 100-seat classroom at the faculty of Architecture, Chiang Mai University. The physical environment real-time data recorded online every 10 minutes for a year are carbon dioxide (CO2) level, indoor temperature, and relative humidity. The environmental data then are analyzed with the ASHRAE 62.1 standard and the Engineering Institute of Thailand standard for classroom ventilation. The results show that there is no installation of any fresh air intake system, no mechanical fans and no exhausting system from the air-conditioner. Consequently, air change rate of a measured classroom inadequate and the CO2 cumulative level has become risky to health. The peak CO2 level is almost 5,000 ppm at 4.30 pm in the 4-class-continuous day, meaning totally cumulative for more than seven hours. In the worst case, this condition could possibly result in unconsciousness. Although the occupants have responded less severe than in theory, their feedback conforms dizziness, fatigue, and sleepiness after the 2nd class. Thermal comfort status in the classroom was ‘warm’ and ‘slightly warm’, while the air-conditioners were turned on during the classes. The recommendation for IEQ improvement is to re-install the standardised air-conditioning system or to increase ventilation rate by installing at least 12 fans with 300 m/s velocity performance.